Pengaruh Kegiatan Lempar Tangkap Bola Terhadap Motorik Kasar Anak Pada Usia 5-6 Tahun di Paud Anugerah GKPI Pearaja Tarutung - Elsa Konika Panjaitan; Rotua Samosir; Hisardo Sitorus (Institut Nalanda, 2023)
The aim of this research was to determine the effect of ball throwing and catching activities on the gross motor skills of children aged 5-6 years at PAUD Anugerah GKPI Pearaja Tarutung. The method used in this research is a quantitative research method with a pre-experimental type of research in the form of